PERJANJIAN PENETAPAN HARGA DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA (STUDI KASUS PENETAPAN HARGA FUEL SURCHARGE PADA PENERBANGAN DOMESTIK DI INDONESIA) - , MARIA WRESTI ANDRIYANI; , Prof. Dr. M. Hawin, S.H., LL.M., Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to (1)To find out whether the application of Article 5 of Law No. 5/1999 on the Price Fixing Agreement which is established by the Commission/KPPU along with its analysis of the Commission/KPPU Verdict No. 25/KPPU-I/2009 is right (2)To determine whether the price fixing agreements of FuelSurcharge on domestic flights in Indonesia which is reviewed in terms of the provisions of the cartel according to Law No. 5/1999 was a form of cartel. This research is a normative-empirical, which is descriptive, and aims to provide the data as thoroughly as possible about condition or indication of existing law. Normative-empirical legal research examine the execution or the implementation of the provisions of positive law (legislation) on any particular legal events that occur in the community to achieve its intended purpose. The assessment aims to determine whether the results of the application in the event that legal or not in accordance with the Act. The collected data was analyzed qualitatively, by classifying materials obtained in accordance with the laws of the problems in this study, and then was analyzed on which to make cocnclusions. Based on the research that has been conducted, concluded that: (1)There is inconsistency in the application of Article 5 of Law No. 5 of 1999 on the Commission/KPPU Verdict No.25/KPPU/I-2009. Commission/KPPU has undertaken a fundamental mistake on the element of "Relevant Market". If the Commission/KPPU considers that the product market is aviation services, then that should be examined is how the rivalry with other services like transport services by land or sea transportation services. (2)Fuel surcharge pricing establishment which was undertaken by nine airlines with INACA is not a cartelâs configuration as alleged by Commission, because the element of "agreement with rival businesses" in Article 5 and Article 11 are not fulfilled. It is strengthened by the Central Jakarta District Court Verdict on February 28, 2011 and the Verdict of the Supreme Court on February 27, 2012 which revoked the Commission/KPPU Verdict No.25/KPPU/I-2009